KEMAMPUAN BELAJAR MANDIRI MAHASISWA UNIVERSITAS NEGERI JAKARTA - Suprayekti Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
This research was intended to find out what and how the independent learning competency of the students of State University of Jakarta. Data were collected by using questionnaires. The scope of study was limited to the students of School of Education, State University of Jakarta. Samples were chosen by using purposive sampling technique. Research findings show that: (1) based on independent learning method, all students of State University of Jakarta can implement independent learning, (2) based on the goals of independent learning the students are expected to have responsibility to themselves and the implementation of independent learning. Further, this research gives some suggestions such as: (1) university, especially School of Education should provide infrastructure, trainings, and compatible components; (2) the lectures should have appropriate knowledge and concept in independent learning; and (3) the students should practice constructivism and active learning as well as to learn without depending on other people.